2001
DOI: 10.1046/j.1365-8711.2001.04937.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of seeing on Sérsic profiles - II. The Moffat PSF

Abstract: A B S T R A C TThe effects of seeing on Sérsic r 1/n profile parameters are extensively studied using a Moffat function. This analytical approximation to the point spread function (PSF) is shown to provide the best fit to the PSF predicted from atmospheric turbulence theory when b , 4:765. The Moffat PSF is additionally shown to contain the Gaussian PSF as a limiting case ðb ! 1Þ. The Moffat function is also shown to be numerically well behaved when modelling narrow PSFs in HST images. Seeing effects are compu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(162 citation statements)
references
References 17 publications
2
159
0
1
Order By: Relevance
“…Mass Maps Numerous studied have shown that the ability of recovering intrinsic galaxy properties from observed flux distributions depends strongly on the image S/N, resolution and even on the intrinsic properties of the galaxies themselves (Disney 1976;Schweizer 1979;Franx et al 1989;Impey & Bothun 1997;Trujillo et al 2001;Graham et al 2005;Cameron & Driver 2007;Bailin & Harris 2008;Graham & Worley 2008;Maller et al 2009;Carollo et al 2013a;Cibinel et al 2013a). Our mass-based measurements will also be affected by similar limitations.…”
Section: Systematic Uncertainties In the Reconstructedmentioning
confidence: 99%
“…Mass Maps Numerous studied have shown that the ability of recovering intrinsic galaxy properties from observed flux distributions depends strongly on the image S/N, resolution and even on the intrinsic properties of the galaxies themselves (Disney 1976;Schweizer 1979;Franx et al 1989;Impey & Bothun 1997;Trujillo et al 2001;Graham et al 2005;Cameron & Driver 2007;Bailin & Harris 2008;Graham & Worley 2008;Maller et al 2009;Carollo et al 2013a;Cibinel et al 2013a). Our mass-based measurements will also be affected by similar limitations.…”
Section: Systematic Uncertainties In the Reconstructedmentioning
confidence: 99%
“…where the radial scale length α and the slope β are free parameters, which can be related to the seeing by the relation FWHM= 2α √ 2 1/β − 1 (see also Trujillo et al 2001). This method has proved to be suitable in our case due to the presence of extended wings in the PSFs.…”
Section: Data From the Ohp Observatorymentioning
confidence: 92%
“…However, a Moffat function is a better fit to the seeing, with only 42% EE in the seeing FWHM (e.g. Trujillo et al 2001 3 ). with HARPS and NIRPS, and 0.5-0.95 µm for the NIRPS alone mode.…”
Section: Ngs Magnitudementioning
confidence: 99%